2018
DOI: 10.1002/acm2.12405
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose rate intracavitary brachytherapy pretreatment dwell position verification using a transparent applicator

Abstract: PurposeThe major errors in HDR brachytherapy are related to treatment distance, almost all of which are caused by incorrect applicator information. The aim of this study is to propose a quick pretreatment verification method to evaluate channel length and dwell position with a transparent applicator, which, in addition, is suitable as an education tool to assist in the understanding of the applicator structure.MethodsA transparent applicator model was fabricated using a three‐dimensional printer and transparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…According to reports from the US NRC and ICRP 97 and the Japanese user community, many of the reported events were related to inappropriate channel length, incorrect residence location, incorrect step size, and incorrect prescription volume. Most causes of these events were human errors that were related to treatment planning or commissioning [1,5,10]. Few reports Reports also revealed the incidence of all brachytherapy events to be 0.02-1.6% [6,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to reports from the US NRC and ICRP 97 and the Japanese user community, many of the reported events were related to inappropriate channel length, incorrect residence location, incorrect step size, and incorrect prescription volume. Most causes of these events were human errors that were related to treatment planning or commissioning [1,5,10]. Few reports Reports also revealed the incidence of all brachytherapy events to be 0.02-1.6% [6,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of this accident was that the input channel length was continuously incorrect; the treatment was performed 3 cm off the tip of the ovoid applicator tip. In Japan, 9 HDR brachytherapy-related events occurred between March 2008 and March 2017 (reported by a single manufacturer's user community) [10]. Most of those events were classified as occurring because of the wrong dwell position or dwell time of the source.…”
Section: Purposementioning
confidence: 99%
“…To the best of our knowledge, no report has described HDR-BT QA tools having these functions. [11][12][13][14][15][16] Our QA tool allows for verification of actual source positions, as the interaction between Ir-192 gamma ray and radiopaque markers blackens radiographic films (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Since errors related to applicator offset cannot be detected by mechanical testing alone (e.g., verification of dummy source positions using radio- Several studies have reported methods for HDR-BT source position verification. [11][12][13][14][15][16][17] Radiochromic dosimetry films have been used to verify active source positions for HDR-BT, 11 although a lack of information on reference positions makes it difficult to quantitatively assess source positions. To address this issue, some have suggested methods to add information on films, such as by superimposing a source autoradiograph on a radiograph of dummy sources inside the applicator, 12 manually marking reference positions, 13 or utilizing a tungsten wire.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation